An Empirical Evaluation of Budget Implementation on Economic Development in Nigeria - C, Okafor M.; Etim, Raphael S; Efanga, Udeme Okon (Journal of Asian Multicultural Research for Economy and Management Study, 2021)
One of the primary goals of this study was to explore how a budget review approach may affect Nigeria’s economic development. The reasoning was that the Nigerian economy was being challenged by a variety of imbalances in budget creation and implementation. The study strategy was based on events that occurred after the study was completed, and the data used in the study came from the Central Bank Statistical Bulletin and the Federal Ministry of Finance. A model was constructed based on both empirical and theoretical investigations in order to achieve this broad goal. The HDI, which was utilized as a measure of development, was the dependent variable in the model. The government’s capital budget, recurrent budget, and the speed of annual budget implementation were the other independent variables in the model. They examined data using the Auto Regressive Distributed Lag (ARDL) Model, diagnostic tests such as the test of normality, auto correlation test, and heteroskedasticity test, which proved the validity and reliability of the model they chose; inferential results reveal that the use of budget evaluation had a positive and significant impact on the Nigerian economy. According to the study’s suggestions, Nigeria’s government should try to increase capital and recurrent expenditures in its annual budget, both of which have a significant impact on economic development. Finally, the government should work to build budget monitoring and review infrastructure that will aid in the effective implementation of large budget expenditures while also ensuring compliance with legal procedures.